2023
DOI: 10.5021/ad.22.070
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Prospective, Split-Face Pilot Study to Evaluate the Safety and Efficacy of 532-nm and 1,064-nm Picosecond-Domain Neodymium:Yttrium-Aluminum-Garnet Lasers Using a Diffractive Optical Element for Non-Ablative Skin Rejuvenation: Clinical and Histological Evaluation

Abstract: Background The advent of fractionated picosecond (ps) lasers has provided an opportunity to explore new ways of creating microinjuries in the skin to induce skin rejuvenation. Objective To compare the efficacy and safety of diffractive optical element (DOE)-assisted ps neodymium: yttrium-aluminum-garnet (Nd:YAG) lasers with 532-nm and 1,064-nm wavelengths (532-nm and 1,064-nm Nd:YAG P-DOE) using a novel fractional handpiece for the treatment of photoaged skin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Han and colleagues 47 conducted a study comparing 2 different laser wavelengths, the 532-nm and 1,064-nm Nd:YAG P-DOE, for skin rejuvenation. Their findings demonstrated that the 532-nm Nd:YAG P-DOE was more effective in improving dyspigmentation, although no significant differences were observed for other evaluated aspects.…”
Section: Resultsmentioning
confidence: 99%
“…Han and colleagues 47 conducted a study comparing 2 different laser wavelengths, the 532-nm and 1,064-nm Nd:YAG P-DOE, for skin rejuvenation. Their findings demonstrated that the 532-nm Nd:YAG P-DOE was more effective in improving dyspigmentation, although no significant differences were observed for other evaluated aspects.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, fractional picosecond lasers produce nonthermal, photomechanical stress in the dermis and promote fibroblast proliferation (Tanghetti, 2016;K et al, 2021). Recent ex vivo animal and clinical studies also support that 532-nm and 1,064-nm picosecond Nd:YAG lasers may improve photoaged skin (Yim et al, 2020;Connor et al, 2021;Han et al, 2023). In addition, various lasers including low fluence Q-switched Nd:YAG lasers, Q-switched ruby lasers, and Q-switched alexandrite lasers are effective for treating aging-related pigmentation through selective photothermolysis of melanosomes (Anderson and Parrish, 1983;Sadighha et al, 2008;Vachiramon et al, 2016).…”
Section: Energy-based Devicesmentioning
confidence: 99%